Identifikasi Serangga Hama pada Tanaman Cabe di Organ Ilir Sumatra Selatan - Novita Sari, Karlinda; Ayu, Ardia; Wahyuni, Dini; Faraszahy, Dwiki; Aristva, Putri; Intania, Try; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Sari KN, Ayu A, Wahyuni D, Farazahy D, Asrista P, Intania T, Umayah A, Gunawan B, Arsi A. 2022. Identification of insect pests on chili in Ogan Ilir, South Sumatera. In: Herlinda S et al.(Eds), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 824-831. Palembang: Penerbit & Pencetakan Universitas Sriwijaya (UNSRI).Chili is an agricultural plant that is often encountered in everyday life. The productivity of chili plants depends on climate, environment, as well as pests and diseases. In several villages in Ogan Ilir Regency that we surveyed, there were several insect pests on chili plants such as aphids, ladybugs,rice bug, fruit flies and seen from some of their attacks. The purpose of this study was to identify and identify insect pests that exist in chili plants in the villages that we surveyed. This research was conducted in three villages, namely Tanjung Pering Village, Tanjung Baru Village, and Lubuk Sakti Village, Ogan Ilir Regency. The research method that we use is direct method, namely by shaking method, sweep net, and some are caught directly. The results from our survey found insect pests in the form of ladybugs, rice bug, red mites, aphids, and fruit flies. Symptoms of attack from each of these insects are that aphids cause symptoms that make the leaves on chili plants become wrinkled, yellowish and twisted so that plant growth is stunted or stunted. In fact, plants can wither and die. In insects, mites cause symptoms such as leaving a shiny brown color on the underside of the leaves. And attacks on fruit flies, which are symptoms of fruit fly attacks on chili plants are marked by a black dot at the base of the fruit. The population of insect pests that were most commonly found was in the village of Tanjung Pering.Of the various insect pests on chili, physical/mechanical control and selective use of pesticides are needed so as not to interfere with the activity of predatory insects and parasitoids.